PENGARUH NET PROFIT MARGIN (NPM), RETURN ON ASSET (ROA), DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN SAHAM - Siska Widia Utami (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2020)
The purpose of this study was to examine the influence of the Net Profit Margin (NPM), Return On Asset (ROA), and Debt to Equity Ratio (DER) on Stock Returns. Teknik analisis data yang digunakan dalam penelitian ini adalah analisis regresi linear berganda. This research use causality method. The population in this study are consumer goods industry sector manufacturing companies are listed on Indonesia Stock Exchange in 2015-2017. The data chosen using random sampling method. Total sample in this research as many as 69 companies and independent variables: Net Profit Margin (NPM), Return On Asset (ROA), and Debt to Equity Ratio (DER), and the dependent variable: Stock Returns. The results showed that: (1) Net Profit Margin (NPM) has no significant effect on the Stock Returns. (2) Return On Asset (ROA) and Debt to Equity Ratio (DER) has significant effect on the Stock Returns